Investigation Of Junior And Senior High School Students' Attitudes Towards Correcting Mistakes : A casse Study in Guilin - Xinxing Deng; Ying Zhou; Cunhua Liu (Universitas Pahlawan Tuanku Tambusai, 2020)
Students' attitudes towards correcting mathematics wrong questions affect the effect of mathematics learning to a certain extent. Focusing on students' attitudes towards correcting maths wrong questions, discovering the problem from the root cause can provide an important basis for correcting behavior. This research uses quantitative methods. the data were taken using a questionnaire. The sample of this study was 622 students in Guilin, China. The results of the questionnaire were processed using Microsoft Word and SPSS. the students filled out a questionnaire Attitudes towards Correcting Mathematics Wrong Questions Scale to investigate the attitudes of junior and senior high school students to correcting mathematics wrong questions from the three dimensions of cognition, behavior tendency and emotion. This research found 1) the overall level of Junior and senior high school students' attitudes towards correcting mathematics wrong questions is relatively high; 2) There are differences in the three dimensions, that is, cognitive level>emotional level>behavioral tendency; 3) there are significant differences in the attitude of correcting mathematics wrong questions in gender, whether or not they are student leaders, whether the head teacher is a math teacher, and grade; 4) And there is a significant correlation between each dimension and mathematics academic performance; 5) the attitude of correcting mathematics wrong questions significantly positively affects mathematics academic performance.